Back Cover: Modification of Diet to Reduce the Stemness and Tumorigenicity of Murine and Human Intestinal Cells. Issue 19 (4th October 2022) - May, Stephanie; Greenow, Kirsty R.; Higgins, Adam T.; Derrick, Anna V.; Taylor, Elaine; Pan, Pan; Konstantinou, Maria; Nixon, Colin; Wooley, Thomas E.; Sansom, Owen J.; Wang, Li‐Shu; Parry, Lee
Abstract : Mol. Nutr. Food Res . 2022, 66, 202200234 DOI: 10.1002/mnfr.202200234 Black raspberries (BRBs) play a role in colorectal cancer chemoprevention. The number of intestinal stem cells, the cells of origin of colorectal cancer, are reduced following a BRB diet. This decreases the chance of a mutation occurring within these stem cells and subsequently reduces the risk of developing colorectal cancer. This is reported by Stephanie May, Lee Parry, and co‐workers in article number 2200234 .